Body composition profiling in a Dutch sarcoidosis population - Cremers, Johanna P; Drent, Marjolein; Elfferich, Marjon D; Nelemans, Patty J; Wijnen, Petal A; Witteman, Ben J; Schols, Annemie M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Muscle atrophy is a common problem in many chronic inflammatory diseases. It may occur as part of a generalized wasting process (cachexia) or be hidden due to preservation of fatmass (sarcopenia, sarcopenic obesity). Objectives: The aim of this study was to assess the prevalence of cachexia and muscle atrophy in sarcoidosis and their association with disease activity and severity. Methods: A cross-sectional study was performed in 423 sarcoidosis patients. Fat-free mass was assessed as an indirect measure of muscle mass by bioelectrical impedance analysis. Patients were stratified based on body mass index (BMI) and fat-free mass index (FFMI).Muscle atrophy was defined as FFMI